Evaluasi Penyelenggaraan Webinar: Strategi UMKM Korea Selatan Bertahan Dalam Pandemi COVID-19 - Nadya Megawati Rachman (Pusat Pendidikan dan Pelatihan Perdagangan, 2020)
One of the economic sectors that has been significantly affected by the COVID-19 pandemic in Indonesia is the middle and lower class businesses, which are often referred to as Medium, Small and Micro Enterprises (MSMEs). The Trade Education and Training Center, has an important role in being able to contribute to the wider community, by providing information and knowledge and new enthusiasm in facing this pandemic, one of which is for MSMEs in Indonesia by holding various trainings and seminars which are held online (webinars) which accessible to all MSME players in Indonesia. Pusdiklat Trade held a webinar with the theme